2023
DOI: 10.1002/mp.16098
|View full text |Cite
|
Sign up to set email alerts
|

Spot scanning proton arc therapy reduces toxicity in oropharyngeal cancer patients

Abstract: Background: Proton arc technology has recently shown dosimetric gains for various treatment indications. The increased number of beams and energy layers (ELs) in proton arc plans, increases the degrees of freedom in plan optimization and thereby flexibility to spare dose in organs at risk (OARs). A relationship exists between dosimetric plan quality, delivery efficiency, the number of ELs -and beams in a proton arc plan. Purpose: This work aims to investigate the effect of the number of beams and ELs in a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Based on this concept, publications from different research institutions have shown the potential clinical benefit of proton arc therapy for a wide range of clinical indications, 55–62 drawing significant interest among radiation oncology communities, including the ESTRO, 63 AAPM, 64 and PTCOG 65 . Multiple international consortiums have been established, aiming to join‐force in pushing the technique forward 66,67 .…”
Section: Opening Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this concept, publications from different research institutions have shown the potential clinical benefit of proton arc therapy for a wide range of clinical indications, 55–62 drawing significant interest among radiation oncology communities, including the ESTRO, 63 AAPM, 64 and PTCOG 65 . Multiple international consortiums have been established, aiming to join‐force in pushing the technique forward 66,67 .…”
Section: Opening Statementsmentioning
confidence: 99%
“…8 As a result, the concept of particle arc therapy was not at the center of the research development until the introduction of the first robust spot-scanning particle arc therapy optimization algorithm 8 and the demonstration of its feasibility using a clinical system. 54 Based on this concept, publications from different research institutions have shown the potential clinical benefit of proton arc therapy for a wide range of clinical indications, [55][56][57][58][59][60][61][62] drawing significant interest among radiation oncology communities,including the ESTRO, 63 AAPM, 64 and PTCOG. 65 Multiple international consortiums have been established, aiming to join-force in pushing the technique forward.…”
Section: Opening Statementsmentioning
confidence: 99%
“…This approach is similar, but not identical to the energy layer reduction (ELR) technique. 8,9 In ELF the arc is set up by a start and stop gantry angle, a number of irradiation directions, an initial and final number of energy layers. Throughout the optimization, the lowest weighted energy layers are filtered out to reach the final number of energy layers.…”
Section: Patients and Treatment Planningmentioning
confidence: 99%
“…When this method was employed to 10 oropharyngeal cancer patients, it was found that 360 layers distributed over 30 directions produced near optimal plans with reduced toxicity to normal tissue. 9,10 The disadvantage of this method is that a large number of beams will lead to very long and possibly even unacceptable treatment times, if introduced using conventional IMPT delivery. Technological advances, such as automatic sequencing of consecutive IMPT beams or delivery as a single stepand-shoot arc beam with no additional time between discrete directions other than the rotational time, could remove part of this problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation